The Importance of Employee Motivation to Develop Pempek Bain Business - Intan Fadillah; Siti Syaadah Muplihat; Dwi Epty Hidayaty (PT FORMOSA CENDEKIA GLOBAL, 2023)
To increase the work productivity of employees, we need encouragement from management so that employees want to improve their performance so that productivity will increase. The purpose of this research is to determine employee motivation, employee productivity and the relationship between employee motivation and Pempek Bain employee productivity. The approach used in this study is a qualitative approach with descriptive and observational methods. Observational data collection techniques, interviews and studios and documentation. employees in different positions. proper work, d) distributing prizes. (3) related to the motivation of pempek bain employees in increasing work productivity through good leadership management.